Strategies and the tactics of mobilisation: opposition political parties in Malaysia, 1982-2003 - Omar, Muhamad Fuzi (Lambert Academic Publishing, 2015)
This study examines the strategies and tactics of political mobilisation by the opposition political parties in Malaysia during Mahathir’s era. The study is based on two major arguments. First, the electoral performance of the opposition political parties is related to the ways in which they accommodate each other objectives. Second, opposition strategies and tactics have evoked different types of responses by the members of ruling coalition, Barisan Nasional. This study is based upon the framework which explains the features of parliamentary and extra-parliamentary strategies. It examines the linkage between parliamentary and extra-parliamentary strategies, the performance of opposition parties and the responses of the ruling coalition. Data for this study come from official electoral results, parliamentary reports, the opposition parties’ publications, and interviews with some of the key party leaders and members. Main stream newspapers and opposition newsletters have also content analysed. The study found the following: One opposition parties were not effective in achieving their goals when they pursued divergent strategies. Two, opposition parties did combine and pursued similar strategies and succeeded in mobilising mass support during the elections. However, such cooperation has been rare and did not last long. Three, the government response of the ruling coalition varied. They were repressive when the opposition resorted to extra-parliamentary strategy. However, they responded positively to some of the demand made by the opposition in the parliament.